The Generation and Study of a Gold‐Based Chemobrionic Plant‐Like Structure. Issue 1 (30th June 2020) - Zissi, Georgia D.; Angelis, George; Pampalakis, Georgios
Abstract: The generation of chemical gardens based on tetrachloroauric acid and silicate is presented. The structures were studied with SEM, XRD and micro‐Raman spectroscopy and a new mechanism that participates in their development was revealed. Specifically, the structures were decorated with metallic Au that is derived during the process of plant‐like growth. Probably, the instability of gold salts and hydroxides on silica templates accounts for their reduction to metallic Au. Abstract : Watch your garden grow : The reaction between a HAuCl4 crystal in a silicate solution results in the growth of gold‐decorated plant‐like tubes. The chemical garden were studied using SEM, XRD and micro‐Raman spectroscopy.